Reciprocating subsurface-flow constructed wetlands: a microcosm treatability study - Leslie Behrends; Laura Houke; Earl Bailey; Pat Jansen (Water Science and Technology, 2022)
Two batch-loaded microcosm treatability studies of eight days' duration (192 hours) were conducted concurrently from July 26 through August 3 in an environmentally controlled greenhouse at the Tennessee Valley Authority's (TVA) Constructed Wetlands Research Facility in Muscle Shoals, Alabama, USA. These, the first of five treatability studies, were conducted in batch-loaded wetland microcosms, with and without reciprocation. Reciprocation refers to the process of filling and draining paired wetland cells on a recurrent and timed basis to facilitate passive aeration of fixed microbial biofilms during the drain phase and oxygen depletion during the fill phase. The study was designed to simultaneously evaluate the influence of three treatment parameters with respect to removal dynamics of chemical oxygen demand (COD), total ammonia-nitrogen (TAN), nitrate-nitrogen, and orthophosphorus. The treatment parameters evaluated included four COD concentrations, two reciprocation cycle times, and the presence or absence of reed canary grass (Phalaris arundinacea), a plant with an anoxic rootzone. Temperature, pH, dissolved oxygen, electrical conductivity, redox potential, and evapotranspiration were also monitored. Results showed that treatments with reciprocation vs. no reciprocation provided significantly enhanced aerobic and anoxic treatment of wastewater and improved removal of COD and ammonium, irrespective of initial COD concentrations or planted vs. not planted with P. arundinacea. Treatments with P. arundinacea had less accumulation of nitrate nitrogen; less than 0.4 mg/L., while reciprocating treatments without P. arundinacea accumulated from 15–26 mg/L nitrate nitrogen over the 192-hour treatment period. HIGHLIGHTS Reciprocation improved several aerobic and anoxic wastewater treatment processes.; Reciprocation improved nitrification.; Reciprocation enhanced denitrification.; Canary grass, Phalaris arundinacea, improved denitrification.; Reciprocation has potential to be energy efficient and land conserving as compared to traditional subsurface flow constructed wetlands.;